2009
DOI: 10.1108/14720700910964334
|View full text |Cite
|
Sign up to set email alerts
|

Governance implications of the effects of stakeholder management on financial reporting

Abstract: PurposeThe purpose of this paper is to test whether effective stakeholder management results in transparent financial reporting.Design/methodology/approachThis paper uses a linear model informed by stakeholder theorizing and established measures of stakeholder management, earnings quality, and earnings management.FindingsOrganizations exhibiting effective stakeholder management have higher earnings quality and are less likely to engage in discretionary earnings management.Research implicationsFuture research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Namun demikian, hasil penelitian Idah (2013) di atas berbeda dengan temuan Kurnianingsih (2013) Merujuk pada teori stakeholder, perusahaan ingin memenuhi harapan para stakeholder dengan membuat Sustainability Report yang mendeskripsikan mengenai aktivitas perusahaan dibidang sosial dan masyarakat sekitar (Kumar, 2014). Di sam-ping itu, komite audit sebagai salah satu perwujudan Good Corporate Governance secara empiris dapat meningkatkan corporate environment disclosure (Mattingly, et al, 2009;Sun, et al, 2010).…”
Section: Pengembangan Hipotesis Dan Model Penelitianunclassified
“…Namun demikian, hasil penelitian Idah (2013) di atas berbeda dengan temuan Kurnianingsih (2013) Merujuk pada teori stakeholder, perusahaan ingin memenuhi harapan para stakeholder dengan membuat Sustainability Report yang mendeskripsikan mengenai aktivitas perusahaan dibidang sosial dan masyarakat sekitar (Kumar, 2014). Di sam-ping itu, komite audit sebagai salah satu perwujudan Good Corporate Governance secara empiris dapat meningkatkan corporate environment disclosure (Mattingly, et al, 2009;Sun, et al, 2010).…”
Section: Pengembangan Hipotesis Dan Model Penelitianunclassified
“…Siegel and Vitaliano (2007) distinguished between strategic and public CSP, theorizing more reliable economic returns from strategic forms than from public forms of CSP. Also, Mattingly, Harrast, and Olsen (2009) examined effects on accounting practices, especially earnings transparency, on technical benefit, technical harm, institutional benefit, and institutional harm, following measurement protocols established by Mattingly and Berman (2006). These measures combined the distinction between positive and negative aspects of CSP with the distinction between institutional and technical stakeholders.…”
Section: Dimensions and Typologies Of Cspmentioning
confidence: 99%
“…Among the findings were that a company’s tendency toward beneficial social action was positively associated with earnings quality, or transparent reporting, and negatively associated with earnings management, or manipulated reporting. Social harm was negatively related to earnings quality, but not to earnings manipulation (Mattingly et al, 2009). Another study found that environmental concern was positively related to overstatement of earnings, whereas environmental strength and neutrality were unrelated to earnings management (Heltzer, 2011).…”
Section: Outcomes Of Cspmentioning
confidence: 99%
“…As a result, using FVA to prepare firms' assets and liabilities estimates needs a third party to ensure the reliability and credibility of the fair values prepared by managers (Griffith et al, 2015;Lachmann et al, 2015). Auditors, in this case, should act as a monitoring tool to assist shareholders in making decisions by minimising the problem of asymmetric information caused by the agency conflict (Mattingly et al, 2009;Sangchan et al, 2020). The ongoing debate regarding the major role of FVA on the crisis had implications for accounting practices particularly the auditing profession.…”
Section: Fair Value Contribution To the Gfcmentioning
confidence: 99%